Potential Role of Clostridium Difficile and Clostridium Perfringens as A Cause af Diarrhea in Horses - Eman ,F. Farag (Egyptian Society for Animal Management, 2019)
Diarrhea is a major clinical problem affecting foals and horses at different ages which can be fatal and cause great economic losses particularly in foals. The aim of this study was to identify Clostridium perfringens and Clostridium difficile involved in enteric infections and the associated virulence factors in diarrheic foals and horses. Thirty fecal samples were examined for identification of C.perfringens and C.difficile (bacteriological culturing, microscopical examination, count and molecular detection). C.perfringens was isolated from young horses less than 6 months age in an incidence of 46.7% with count ranged from 1.3×104- 5.6×108 cfu/g, while from horses of 6 months to one year, it was 20% with count ranged from 1.7×104- 1.9×106 cfu/g, on the other hand, 13.3% with count ranged from 1.4×103- 2.5×104 cfu/g was the incidence of C.perfringens in horse more than one year. C. difficile was not detected in all examined samples. C.perfringens type A was the most predominant type detected in an incidence of 58.3% then type B (4.7%). All C.perfringens isolates were sensitive to penicillin, nitromedazole, fluramfenicole and ceftiofur and all are resistant to oxytetracycline. Based on the high count, eight C.perfringens isolates were chosen to be molecular characterized for the presence of some virulence factor genes which included ; cpa, cpb2, cpe and netF toxin genes. All examined isolates have cpa (alpha) and cpb2 (beta 2) toxin genes, 5/8 isolates were found to have netF gene while only 2 isolates harbored cpe (enterotoxin gene). C. difficile tpi gene was not detected in all examined samples (10). This study may throw the light on the synergistic effect of β2 and net F toxins together with alpha toxin on induction of enterocolitis in horse.